The combination of a SPOC with evaluative interactive learning in dental adhesion education: a comparison with a lecture-based learning mode - Siqi Wang; Di Yang; Wenbo Zhao; Xiaoyuan Yan; Xiyue Zhang; Wenqing Gao; Jiajie Guo (BMC Medical Education)
Abstract Background Dental education focuses on the cultivation of students’ diagnosis and treatment ability, and improving the teaching effect is an important prerequisite for achieving this goal. This study evaluated whether the combination of a small private online course (SPOC) with evaluative interactive learning (EIL) could effectively enhance students’ engagement in learning and improve their ability to understand and apply knowledge pertaining to dental adhesion. Methods A total of 79 undergraduate students were divided into an EIL group and a lecture-based learning (LBL) group. Students’ levels of participation were evaluated in terms of the frequency of their speech and interaction. Students’ ability to apply their basic knowledge, competency knowledge, and operational skills were assessed with a written test and an operation test. Students’ perceptions were assessed via questionnaires. Results Students in the EIL group presented higher levels of engagement and interaction frequency than did students in the LBL group. The students in the EIL group outperformed those in the LBL group on the ability analysis test and operation test, whereas no significant differences were observed between the students in these two groups with respect to the basic knowledge test. In addition, the scores obtained by the students in the EIL group exhibited a notable shift toward a higher range. The students in the EIL group also exhibited a better ability to employ various effective bonding methods. The questionnaire results revealed that EIL can promote active learning among students without increasing the burdens that they face. Conclusion The use of this combination of a SPOC with EIL as an approach to education in dental adhesion can achieve good results, including significant improvements in students’ learning participation, clinical thinking, and operational abilities as well as their willingness to learn actively.